Exploring Tumor Immune Microenvironment and Its Associations With Molecular Characteristics in Melanoma - Wang, Jiangyuan; Peng, Cong; Dai, Wentao; Chen, Xiang; Meng, Jing; Jiang, Taijiao (Frontiers in Oncology, 2022)
The tumor microenvironment (TME), which involves infiltration of multiple immune cells into the tumor tissues, plays an essential role in clinical benefit to therapy. The chemokines and their receptors influence migration and functions of both tumor and immune cells. Also, molecular characteristics are associated with the efficacy of melanoma therapy. However, there lacked exploration of immune characteristics and the association with molecular characteristics. To fill in these gaps, we employed the currently available 569 melanoma samples that had both the genomic and transcriptional data, and took the advantages of the developed immune and molecular subtyping methods to dissect the characteristics of immune infiltration, the interactions of chemokines and their receptors under immune cells, and the correlation of molecular and immune characteristics. Our work contributes to the understanding of melanoma immune microenvironment and the association with molecular characteristics, which will facilitate the development of new therapeutic strategies for melanoma.